Acute lymphoblastic leukemia in National Children’s hospital From January, 2017 to June, 2018 - Lan, An Thuy; Quang, Vu Dinh; Huy, Nguyen Xuan; Nghiem, Luong Thi; Ha, Dang Thi; Ngoc, Ngo Diem; Lan, Bui Ngoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Acute Lymphocytic leukemia (ALL) is the most common cancer in children. Cytogenetics analysis plays an important role in classification and prognosis in ALL patient. Objectives: to define the frequency of chromosomal abnormalities of ALL patients in children. Methods: 139 patients were diagnosed with ALL at National Children’s Hospital- Hanoi- Vietnam from January/2107 to June/2018. Karyotype analysis and Fluorescence hybridization (FISH) techniques were applied to detect chromosomal abnormalities. Results: The proportion of male children is higher than that of females, at the age group of 1-10 years, accounting for 86.33%. Immune type predominant group prescursor B (preB) accounted for 92.09%. The frequency of cytogenetic abnormalities, including numerical and/or structural changes, was 36.70%. Conclusion: Normal karyotype was more frequent in our study. The frequencies of some cytogenetic abnormalities such as t(9;22), t(1;19), MLL- rearranged in our study were comparable to those reported in the literature.